Fire Disaster Preparedness Analysis at Bantuas Khansa Jaya Petrol Station, Samarinda City - istiarto; Suwignyo; Nova Kristin (Journal of Innovative and Creativity, 2025)
Fire is a disaster that no one wants, because it causes a big impact on the community, namely material losses, and can take a person's life. Public Fuel Filling Stations (SPBU) have a fire risk because they store flammable materials. According to World Health Organization (WHO) data in 2004, more than 2.3 million lives were lost and property losses of 4.5 billion USD due to fuel misuse. Fire control efforts are mitigation, early warning, and preparedness measures. The purpose of this study is to determine how to prepare for fire disasters at the Bantuas Khansa Jaya petrol station in Samarinda City. This type of research uses a qualitative method with a phenomenological approach. The sample in this study is employees at the Bantuas Khansa Jaya petrol station, Samarinda City, with a sample number of 3 respondents. For sampling techniques, purposive sampling is used. The results of this study show that emergency response procedures at Bantuas Khansa Jaya petrol stations do not exist and are not in accordance with the policy; for the active fire protection system only, there are fire extinguishers, and those that are not yet available at the Bantuas Khansa Jaya petrol station are hydrants, sprinklers, detectors, and alarms. In this study, it is expected to be a reference for the owners of related agencies, namely the Bantuas Khansa Kaya petrol station, so that they can make emergency response procedures policies and complete the facilities of their active fire protection systems.